2021
DOI: 10.18203/2394-6040.ijcmph20210791
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices towards COVID-19: a cross-sectional study among nursing and midwifery students in Jalingo, Nigeria

Abstract: Background: The coronavirus disease (COVID-19) infection rate and mortality among Nigerian health care workers appear to be on the increase. Aside from health workers, it has caused millions of infections and deaths worldwide.  This study determined the level of knowledge, attitude, and practices of nursing and midwifery students towards COVID-19 in a North-Eastern Nigerian state.Methods: A total of 156 respondents were involved in this institutional-based cross-sectional study, conducted after the lockdown pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Also a similar study was conducted in North Eastern Nigeria [ 9]. concerning the knowledge, attitude, and practices of nursing and midwifery students about COVID-19 displayed good knowledge, positive attitudes, and good practices.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Also a similar study was conducted in North Eastern Nigeria [ 9]. concerning the knowledge, attitude, and practices of nursing and midwifery students about COVID-19 displayed good knowledge, positive attitudes, and good practices.…”
Section: Discussionmentioning
confidence: 75%
“…A study was conducted in a North-Eastern Nigerian state to determine the level of knowledge, attitude, and practices of nursing and midwifery students towards COVID-19 displayed decent knowledge, positive attitudes, and decent practices [9]. While a study among Chinese healthcare students (including nursing) revealed that the students had favorable attitudes toward disease treatment but were poor knowledge about COVID-19 and preventative practices with respect to containing the spread of the disease [10].…”
Section: Introductionmentioning
confidence: 99%